Analisis AVO untuk Mengetahui Penyebaran Hidrokarbon Berdasarkan Faktor Fluida (Studi Kasus Lapangan “H” Formasi Talang Akar Cekungan Jawa Barat Utara) - Muhammad Nur Handoyo; Agus Setyawan; Mualimin Muhammad (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
Amplitude versus offset (AVO) inversion analysis can be used to determine the spread of hydrocarbons on seismic data. In this study we conducted AVO on reservoir layer Talang Akar’s formation (TAF). AVO inversion results are angle stack, normal incident reflectivity (intercept), gradient and fluid factor. Angle stack attribute analysis showed an AVO anomaly in the reservoir TAF layer, amplitude has increased negative value from near angle stack to far angle stack. The result of crossplot normal incident reflectivity (intercept) with gradient indicates reservoir TAF layer including Class III AVO anomaly. While the analysis of fluid factor attribute has a negative value thus reservoir TAF layer indicates a potential hydrocarbon.